2011
DOI: 10.3348/kjr.2011.12.6.700
|View full text |Cite
|
Sign up to set email alerts
|

CT Analysis of Retropharyngeal Abnormality in Kawasaki Disease

Abstract: ObjectiveTo retrospectively compare the imaging characteristics of retropharyngeal density and associated findings for Kawasaki disease with those for non-Kawasaki disease, and identify the distinguishing features which aid the CT diagnosis of Kawasaki disease with retropharyngeal low density.Materials and MethodsAmong the enhanced neck CT performed in children less than 8-years old with clinical presentation of fever and cervical lymphadenopathy over a 6-year period, only cases with retropharyngeal low densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 17 publications
(24 reference statements)
1
27
0
Order By: Relevance
“…Previous reports have compared NFKD with typical KD. 9, 10 Others have described radiologic features 11 and laboratory values 12 that could distinguish NFKD from BCL. Our KD Research Center’s extensive database afforded the unique opportunity to describe and compare NFKD, typical KD, and BCL from a single center.…”
mentioning
confidence: 99%
“…Previous reports have compared NFKD with typical KD. 9, 10 Others have described radiologic features 11 and laboratory values 12 that could distinguish NFKD from BCL. Our KD Research Center’s extensive database afforded the unique opportunity to describe and compare NFKD, typical KD, and BCL from a single center.…”
mentioning
confidence: 99%
“…Group A had greater thickness of RLD, greater scores of the RLD extent into the deep neck spaces, greater scores of the adjacent soft tissue changes than Group B. 19 Therefore, KD patients with retropharyngeal space changes have stronger inflammatory reactions than non-KD patients.…”
Section: Discussionmentioning
confidence: 98%
“…11 However, inflammation and edema were considered the main mechanism. 19 Increased microvascular permeability is an initial step of KD, and vascular endothelial growth factor might play a role in the vascular leakage. Increases in vascular leakage cause hypoalbuminemia and noncardiogenic edema.…”
Section: Discussionmentioning
confidence: 99%
“…No KD case was pathologically analyzed according to the database of our university hospital from 2000 to 2016. Previous reports on KD-associated pseudoabscesses suggested that such lesions could originate from systemic vasculitis of microvessels with the tissue edema and inflammation [3,4,10]. The aberrant activation of neutrophils, monocytes/macrophages, CD8 + cells, and IgA-producing plasma cells has been reported to involve the systemic vasculitis in KD patients [1].…”
Section: Discussionmentioning
confidence: 99%
“…The early-appearing manifestation often challenges us to differentiate KD and deep neck infections because the critical lesions may need urgent interventions. KD is suspected when a retropharyngeal abscess is assessed by computed tomography (CT) [3,4,5]. On the other hand, no aspirate samples have been reported that verify abscess formation or fluid collection at the site, even though contrast imaging has indicated ring-enhancing lesions [3].…”
Section: Introductionmentioning
confidence: 99%